Receptor Proteins in Selective Autophagy - Christian Behrends; Simone Fulda (International Journal of Cell Biology)
Autophagy has long been thought to be an essential but unselective bulk degradation pathway. However, increasing evidence suggests selective autophagosomal turnover of a broad range of substrates. Bifunctional autophagy receptors play a key role in selective autophagy by tethering cargo to the site of autophagosomal engulfment. While the identity of molecular components involved in selective autophagy has been revealed at least to some extent, we are only beginning to understand how selectivity is achieved in this process. Here, we summarize the mechanistic and structural basis of receptor-mediated selective autophagy.